Culture simboliche e formazione. Le pratiche immaginali per le professioni sanitarie - Barioglio, Marina (Studi sulla Formazione/Open Journal of Education, 2017)
Health Pedagogy is nowadays deeply contaminated by the ideas that psychologi-cal, social, and economic disciplines offer of its great topics. This has the great advantage to assure clear reference and useful operative protocols helping who works in sanitary services. But often the trend is to abuse of technical categories and languages reducing the sensibility of professionals. This essay shows how the approach of Imaginal Pedagogy uses symbolic art to enrich the educational and therapeutic imaginary of sanitary professionals and to increase their imagina-tive attitude.